Gastroenterology and the provision of care to Panjabi patients in the UK. Issue 3 (13th April 2012) - Mayberry, John Francis; Farrukh, Affifa
Abstract : Panjabi is spoken by 1.3 million people in the UK. It is the second most common language used in the country and is the first choice of 75% of Panjabis. It is becoming more common. For many patients it forms part of the barrier which limits access to gastrointestinal services. The provision of appropriate support services is woeful and yet seldom leads to formal complaints. This review considers the impact of gastrointestinal disorders on the Panjabi community and assesses some of the interventions that could be developed to ensure equity of care.